Profiling of Universitas Ciputra Surabaya Student Satisfaction with Property Management Services - Melissa Christina (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
Increasing competition in service quality, universities must be responsive in providing services to students, because student satisfaction is the top priority for highest education. This study aims to see how much the average level of respondents to the quality of Universitas Ciputra Surabaya Property Management services. Measurements were made using the servqual instrument, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The analysis used in this research is descriptive statistics. The population in this study were active students at Universitas Ciputra Surabaya with a sample size of 186 people. Based on the results of the analysis that has been carried out, it is known that the level of satisfaction of the respondents with an overall average value is 3.97. And of the five factors used, only the Assurance factor gets an average score above 4, while the other four factors get an average score below 4 in the order Tangibles, Reliability, Responsiveness and Empathy as the factors with the lowest level of satisfaction.